TEACHING SPEAKING SKILL BY USING BAMBOO DANCING METHOD TO THE EIGHTH GRADE STUDENTS AT SMP NEGERI 1 LUBUKLINGGAU - Serli Agustina; Syaprizal Syaprizal; Yulfi Yulfi (Universitas Lambung Mangkurat, 2021)
The problem of this study was “Is it significantly effective to use Bamboo Dancing Method to the Eighth Grade Students of SMP Negeri 1 Lubuklinggau in academic year of 2019/2010?” Therefore, the objective of this study was to find out whether or not it is significantly effective to use Bamboo Dancing Method to the Eighth Grade Students of SMP Negeri 1 Lubuklinggau in academic year of 2019/2020 which was divided in to ten classes and the total number was 335 students. The applied method was Pre-experimental method with one group pre-test and post-test design. The writer used cluster random sampling to get the sample. The result was VIII.2 as sample group which consist of 34 students. The instrument of collecting the data was speaking test. The writer applied four techniques in analyzing the data. They were: 1) Individual Score, 2) Minimum Mastery Criteria, 3) Normality test, 4) the Paired t-test. The result of this study: (1) The mean of students’ score in the Pre-test was 29.59, (2)The mean of students score in the Post-test was 78.41, and (3) The result of Paired t-test was 5.69, at one tailed the degree of freedom (df) will be 33 (34-1) with 5% (0.05) significance level, t-table value is 1.692. Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) is accepted. It means that it was significantly effective to use Bamboo Dancing Method to the Eighth Grade Students at SMP Negeri 1 Lubuklinggau in academic year of 2019/2020.